THU0223 The Novel CPLA2 Inhibitor AK106-001616 is a New Category of Anti-Inflammatory/Analgesic Drug Demonstrating Efficacy and Favorable Tolerability in the Treatment of Rheumatoid Arthritis. (23rd January 2014) - Yamanishi, K.; Ellis, B.; Kudo, K.; Kayanoki, T.; Dews, I.; Ostor, A.; Wilson, A.
Abstract : Background: AK106-001616 (AK106) is a selective cytosolic phospholipase A2 (cPLA2 ) inhibitor with a novel mechanism of action as an anti-inflammatory/analgesic drug. Unlike non-steroidal anti-inflammatory drugs (NSAIDs), AK106 inhibits the production of arachidonic acid, the source of inflammatory lipid mediators including prostaglandins (PGs) and leukotrienes (LTs). Inhibition of PGs has been shown to improve the symptoms of rheumatoid arthritis (RA), other chronic inflammatory and pain indications, and the further inhibition of LTs is expected to enhance this effect. Methods: This was a phase IIa, multi-centre study with a randomised, double-blind, triple-dummy, 3-arm, parallel-group, comparator-controlled, repeated-dose design. The study investigated/compared the efficacy, safety, PK and PD of 2 dose levels (100 mg bid and 600 mg bid) of AK106 in patients with active RA to that of naproxen 500 mg bid over a 28 day treatment period. Patients were required to be on background MTX and were randomly assigned to one of the 3 treatment arms. Video capsule endoscopy (VCE) assessment was performed as an optional assessment on Day -1 and Day 29 to investigate the effects of AK106 on the small bowel. Results: A total of 253 patients were randomised and 230 patients completed the 28 day treatment. Patient baseline characteristics were well balanced among the 3 treatment groups. Mean changes in patient assessment of arthritis pain (VAS) from baseline to Day 28 were −18.3 mm in the 100 mg group, −15.9 mm in the 600 mg group and −16.7 mm in the naproxen group. ACR20 response was achieved at Day 28 in 49.4% subjects in the 100 mg group, 47.6% subjects in the 600 mg group and 49.4% subjects in the naproxen group. In terms of the other efficacy variables, AK106 was as effective as naproxen in both the 100 mg and 600 mg groups. The overall incidence of treatment-emergent adverse events (TEAEs) for the 100 mg group was comparable to that for the naproxen group. The incidence of GI related TEAEs in the 100 mg group was slightly lower than the naproxen group. However, the incidence of TEAEs and GI related TEAEs for the 600 mg group was higher. One treatment-emergent serious adverse event was reported in 1 patient in the 600 mg group, and was regarded as unrelated to the study drug. The results of the optional VCE assessment in the small bowel showed that the 100 mg group demonstrated no change from baseline in the mean number of mucosal breaks without haemorrhage however there was a significant increase on Day 29 compared to baseline in the naproxen group (p=0.014, AK106 100 mg vs naproxen). The results for the 600 mg group were similar to those for the naproxen group. Results of the PD marker measurements demonstrated that as expected, while the production of PGs was inhibited by both AK106 and naproxen, the production of LTs was inhibited only by AK106. Conclusions: AK106 was efficacious and well tolerated by patients with RA. The incidence of GI related TEAEs and the significant results of the optional VCE assessment in the 100 mg group suggest that AK106 has a better GI profile compared to naproxen. These results suggest that AK106 may have a role in the treatment of RA patients. Disclosure of Interest: None Declared